Association Between the Acquired Immunodeficiency Syndrome and Infection With Salmonella typhi or Salmonella paratyphi in an Endemic Typhoid Area - Gotuzzo Herencia, José Eduardo (1991)
Eight cases of typhoid and paratyphoid fever were identified during a 4-year period in a cohort of 117 patients who were positive for human immunodeficiency virus in Lima, Peru. Asymptomatic patients with human immundeficiency virus infection and patients with the lymphadenopathy syndrome had a typical clinical presentation and response to therapy. Patients with the acquired immunodeficiency syndrome who were culture positive for Salmonella typhi or Salmonella paratyphi presented with fulminent diarrhea and/or colitis; the two patients for whom at least 2 months of follow-up were available relapsed. In our cohort there were 0.06 cases of typhoid or paratyphoid per patient year of observation; this rate is approximately 60 times that in the general population in Lima, and 25 times that in the 15- to 35-year-old age group. Our data indicate that patients who are positive for human immunodeficiency virus are at significantly increased risk for infection with S typhi and S paratyphi, and suggest that the clinical presentation of these diseases in patients with the acquired immunodeficiency syndrome differs from that seen in immunocompetent hosts. © 1991, American Medical Association. All rights reserved.